Cytototoxic constituents from the bark of Chisocheton cumingianus (Meliaceae). Issue 2 (1st February 2017) - Katja, Dewa Gede; Farabi, Kindi; Nurlelasari,; Harneti, Desi; Mayanti, Tri; Supratman, Unang; Awang, Khalijah; Hayashi, Hideo
Abstract: A new lanostane-type triterpenoid, 3β-hydroxy-25-ethyl-lanost-9(11), 24(24′)-diene (1 ), along with 3β-hydroxy-lanost-7-ene (2 ) and β-sitosterol-3- O -acetate (3 ) was isolated from the stem bark of C. cumingianus . The chemical structure of the new compound was elucidated on the basis of spectroscopic data. All of the compounds were evaluated for their cytotoxic effects against P-388 murine leukemia cells. Compounds1-3 showed cytotoxicity against P-388 murine leukemia cells with IC50 values of 28.8 ± 0.10, 4.29 ± 0.03, and 100.18 ± 0.16 μg/ml, respectively.